Socioeconomic position, symptoms of depression and subsequent mental healthcare treatment: a Danish register-based 6-month follow-up study on a population survey. Issue 10 (3rd October 2018) - Packness, Aake; Halling, Anders; Hastrup, Lene Halling; Simonsen, Erik; Wehberg, Sonja; Waldorff, Frans Boch
Abstract : Objective: Examine whether the severity of symptoms of depression was associated with the type of mental healthcare treatment (MHCT) received, independent of socioeconomic position (SEP). Design: Register-based 6-month follow-up study on participants from the Danish General Suburban Population Study (GESUS) 2010–2013, who scored the Major Depression Inventory (MDI). Participants: Nineteen thousand and eleven respondents from GESUS. Interventions: The MHCT of the participants was tracked in national registers 4 months prior and 6 months after their MDI scores. MHCT was graduated in levels. SEP was defined by years of formal postsecondary education and income categorised into three levels. Data were analysed using logistic and Poisson regression analyses. Outcomes: MHCT included number of contacts with: general practitioner (GP), GP mental health counselling, psychologist, psychiatrist, emergency contacts, admissions to psychiatric hospitals and prescriptions of antidepressants. Results: For 547 respondents with moderate to severe symptoms of depression there was no difference across SEP in use of services, contact (y/n), frequency of contact or level of treatment, except respondents with low SEP had more frequent contact with their GP. However, of the 547 respondents, 10% had no treatment contacts at all, and 47% had no treatment beyond GP consultation. Among respondents with no/few symptoms of depression, postsecondary education ≥3 years was associated with more contact with specialised services (adjusted OR (aOR) 1.92; 95% CI 1.18 to 3.13); however, this difference did not apply for income; additionally, high SEP was associated with fewer prescriptions of antidepressants (education aOR 0.69; CI 0.50 to 0.95; income aOR 0.56, CI 0.39 to 0.80) compared with low SEP. Conclusion: Participants with symptoms of depression were treated according to the severity of their symptoms, independent of SEP; however, more than half with moderate to severe symptoms received no treatment beyond GP consultation. People in low SEP and no/few symptoms of depression were more often treated with antidepressants. The study was approved by The Danish Data Protection Agency Journal number 2015-41-3984. Accessible at: https://www.datatilsynet.dk/fortegnelsen/soeg-i-fortegnelsen/